2011
DOI: 10.1063/1.3626556
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoacoustic solitons in quantum plasma

Abstract: Nonlinear magnetoacoustic waves in collisionless homogenous, magnetized quantum plasma is studied. Two fluid quantum magneto-hydrodynamic model (QMHD) is employed and reductive perturbation method is used to derive Korteweg de Vries (KdV) equation for magnetoacoustic waves. The effects of plasma density and magnetic field intensity are investigated on magnetoacoustic solitary structures in quantum plasma. The numerical results are also presented, which are applicable to explain some aspects of the propagation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…Furthermore, the dependent variables can be expanded in the following form: and Inserting (2.14 a , b )–(2.16) into (2.6)–(2.11), we collect the lowest-order terms, as and Further algebraic manipulations lead to with and Solving together (2.17)–(2.28), the phase speed for magnetosonic waves can be calculated as We see that the phase speed is strongly modified by the relativistic factor and energy ratio due to the degenerate electrons. By neglecting the electron relativistic effects, when , and replacing with in the normalization, the phase speed exactly coincides with the earlier result of Hussain & Mahmood (2011). Equation (2.29) clearly shows that the phase speed in a relativistically degenerate plasma strongly depends on the equilibrium number density as well as on the magnetic field strength .…”
Section: Governing Equations and Modelsupporting
confidence: 85%
See 2 more Smart Citations
“…Furthermore, the dependent variables can be expanded in the following form: and Inserting (2.14 a , b )–(2.16) into (2.6)–(2.11), we collect the lowest-order terms, as and Further algebraic manipulations lead to with and Solving together (2.17)–(2.28), the phase speed for magnetosonic waves can be calculated as We see that the phase speed is strongly modified by the relativistic factor and energy ratio due to the degenerate electrons. By neglecting the electron relativistic effects, when , and replacing with in the normalization, the phase speed exactly coincides with the earlier result of Hussain & Mahmood (2011). Equation (2.29) clearly shows that the phase speed in a relativistically degenerate plasma strongly depends on the equilibrium number density as well as on the magnetic field strength .…”
Section: Governing Equations and Modelsupporting
confidence: 85%
“…In order to solve the KdV equation, we introduce a single moving variable , with being the soliton speed, and arrive at the solution (Hussain & Mahmood 2011). where and are the amplitude and width of the magnetosonic solitons in a relativistically degenerate dense magnetoplasma.…”
Section: Governing Equations and Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…[39] Haas et al [40] have described the QHD model to study the quantum IAWs in e-i plasmas. Hussain and Mahmood [47] studied non-linear magnetoacoustic waves in collisionless homogenous, magnetized quantum plasma. Mushtaq and Khan [45] investigated the properties and stability of IASWs with transverse perturbations in an ultracold e-p-i quantum plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Khan and Haque [46] studied non-linear structures in dissipative e-p-i quantum plasmas and showed that these structures are effectively affected by plasma parameters. Hussain and Mahmood [47] studied non-linear magnetoacoustic waves in collisionless homogenous, magnetized quantum plasma. Haider and Mamun [48] theoretically investigated IASWs and their multi-dimensional instability in a magnetized degenerate plasma.…”
Section: Introductionmentioning
confidence: 99%